MENINGKATKAN KEMAMPUAN BERPIKIR KREATIF MATEMATIS SISWA SMP MELALUI MODEL PEMBELAJARAN SEARCH, SOLVE, CREATE, AND SHARE DAN MODEL PROBLEM CENTERED LEARNING - Pakpahan, Nia Marito; Simbolon, Mangadar (Jurnal Padegogik, 2018)
The ability of creative thinking is one of the important mathematical skills, but fromthe results of previous research indicates the low ability of students' mathematical creativethinking. One of the factors causing the low ability of students' mathematical creative thinkingbecause students who are less active in expressing ideas creatively in solving problems,sparked his ideas, and detailed the problem. Therefore, it is needed a learning model that canaccelerate students' activeness in solving math problems. The author conducted research onthe application of Search, Solve, Create and Share (SSCS) model and Problem CenteredLearning (PCL) model to help improve students' mathematical creative thinking ability. Datacollection techniques use test instruments to measure student learning outcomes. The resultsof this study indicate that: (1) students' creative thinking ability using Search, Solve, Createand Share (SSCS) model is in high category, while PCL model is in moderate category, (2)there is a significant difference between improvement the ability of mathematical creativethinking between students who obtained the Search, Solve, Create and Share (SSCS) modeland students who obtained the PCL model, and (3) the students' response to Search, Solve,Create and Share (SSCS) models and PCL entered into " like ".